2020
DOI: 10.3390/en13051134
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Use of Building Performance Simulation Tools by Recent Graduate Architects and the Deficiencies in Architectural Education

Abstract: This paper examines the actual knowledge regarding Building Performance Simulation Tools (BPSTs) of recent graduate architects in Spain. BPSTs quantify aspects of building performance that are relevant to design, construction, and operation. Recent graduate architects are those who have been awarded a first degree from a university or college and face their first professional experience. This article aims to identify the deficiencies within the current curricula of Spanish universities relating to BPSTs. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…An energy model is similar to an architectural model, except it contains thermal areas instead of elements. Studies have examined how energy simulation has been used by a broad range of users, such as architects, and concluded that technology could be used to make a wider range of decisions [36,37].…”
Section: Case Study Assessments Parametersmentioning
confidence: 99%
“…An energy model is similar to an architectural model, except it contains thermal areas instead of elements. Studies have examined how energy simulation has been used by a broad range of users, such as architects, and concluded that technology could be used to make a wider range of decisions [36,37].…”
Section: Case Study Assessments Parametersmentioning
confidence: 99%
“…Because of the importance of having a deep understanding of the complex links between buildings physics, design and simulation process, our standpoint is that education should train 'experts' or 'performers', even when the profession will require them to be 'consumers'. However, a recent survey carried out in Spain showed that over 70% of architects are BPS 'consumers' and they consider learning BPS challenging [10]. Beausoleil-Morrison (2019) proposed an 'expert' teaching paradigm to modern BPS tool by theorising an experiential learning model [11].…”
Section: Bps In Engineering and Architectural Educationmentioning
confidence: 99%
“…Energies 2020, 13,1941 3 of 15 However, it is desirable to train the 'expert' even with basic simulations, as a smooth and gradual interaction with BPS promotes confidence among students and allows students to move independently to more specific tools at a later stage [10]. Such training-of which the 'control method' is a possible approach-can be implemented already today in existing building physics curricula.…”
Section: Bps In Engineering and Architectural Educationmentioning
confidence: 99%
“…Most of the simulation engines do not include dynamic properties, so developing new tools to calculate the impact of WFG has become a goal of researchers [33,34]. Water is opaque to the near-infrared (NIR) spectrum of light, while its visible transmittance is very high [35].…”
Section: Introductionmentioning
confidence: 99%
“…Complicated simulation engines provide the designer with multiple options, and sometimes they are not useful at an early design stage because decisions have not been made yet. Architects might find better support in simple energy simulation tools than in complicated ones [35,36]. Building information modeling (BIM) has the potential to achieve performance improvements and high-quality construction, and architecture, engineering, and construction (AEC) industries have applied BIM in construction projects over the last few decades [37].…”
Section: Introductionmentioning
confidence: 99%